PERFECT KNOWLEDGE MANAGEMENT SYSTEM AS REQUIREMENT FOR AN ENTERPRISE TO SURVIVE IN MARKET COMPETITION ENVIRONMENT - A. E. Zhukov (Модернизация, инновация, развитие, 2016)
Knowledge, along with skills and abilities forms the concept of professional qualification. Knowledge management as function and type of enterprise management activities includes making the knowledge more practically valuable and creating an active learning environment. Acquisition and assimilation of new knowledge includes six steps discussed in the article: definition, acquisition, selection, storage, distribution, use, development and implementation.